1973
DOI: 10.1136/bmj.1.5844.13
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oestrogen Therapy for Breast Cancer: A Trial of Tamoxifen at Two Dose Levels

Abstract: 13 not aware of evidence to show that prolongation of hospital stay in these patients will result in a lower mortality.We have adopted a conservative attitude to the treatment of complete heart block and all patients were treated medically except for two who were paced electrically. Anterior infarction as a cause of heart block was associated with a higher mortality (78%) than inferior infarction (36%). These figures compare adequately with those of Lassers and Julian (1968) Smyllie, H. C., Taylor, M. P., an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
122
0
3

Year Published

1975
1975
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(126 citation statements)
references
References 2 publications
1
122
0
3
Order By: Relevance
“…The antiestrogen produced response rates of 25-35% in unselected patients comparable to diethylstilbestrol and high dose androgen therapy, the standard endocrine therapies at the time [9,10]. However, fewer side effects were noted with tamoxifen [9,10]. As a result, the drug was approved as a palliative option for the hormonal treatment of breast cancer in the UK in 1973.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…The antiestrogen produced response rates of 25-35% in unselected patients comparable to diethylstilbestrol and high dose androgen therapy, the standard endocrine therapies at the time [9,10]. However, fewer side effects were noted with tamoxifen [9,10]. As a result, the drug was approved as a palliative option for the hormonal treatment of breast cancer in the UK in 1973.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…Studies from our unit have indicated that relapse is not often due to proliferation of an oestrogen-receptor negative (RE-) cell population, since most relapsing tumours contain significant quantities of RE (Taylor et al, 1982). We therefore examined whether relapse or non-response was due to an inadequate effect of endocrine agents on gonadotrophins and steroid hormones in patients treated with tamoxifen, aminoglutethimide (AGT) and danazol, all of which are effective endocrine agents (Ward, 1973;Smith et al, 1978;Coombes et al, 1980a) and are known to lower hormone concentrations (Golder et al, 1976;Santen et al, 1977;Franchimont & Cramilion, 1977).…”
mentioning
confidence: 99%
“…
There was a significantly higher proportion of EGFr+ tumours in the endocrine failure group compared with the control population (P<0.001).EGFr status is a marker for rapid early progression on primary endocrine therapy and the development of non-excisional methods of EGFr analysis would allow better directed therapeutic decisions.The anti-oestrogen drug tamoxifen, and the aromatase inhibitor aminoglutethimide, have been extensively tested in metastatic breast cancer with overall objective remission rates of around 30% (Cole & Todd, 1976;Ward, 1973;Murray & Pitt, 1981; Harris et al, 1986a,b). The lack of serious toxicity in the case of tamoxifen has made this a particularly attractive therapy where quality of life was as important as prolongation (Stewart et al, 1980).
…”
mentioning
confidence: 99%
“…The anti-oestrogen drug tamoxifen, and the aromatase inhibitor aminoglutethimide, have been extensively tested in metastatic breast cancer with overall objective remission rates of around 30% (Cole & Todd, 1976;Ward, 1973;Murray & Pitt, 1981; Harris et al, 1986a,b). The lack of serious toxicity in the case of tamoxifen has made this a particularly attractive therapy where quality of life was as important as prolongation (Stewart et al, 1980).…”
mentioning
confidence: 99%